Pengaruh Penilaian Produk, Promosi dan Layanan COD (Bayar di Tempat) Terhadap Keputusan Pembelian pada Marketplace Shopee di Sidoarjo - Mayangsari Mayangsari; Siti Aminah (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of product rating, promotion, and COD (cash on delivery) service on purchasing decisions at the Shopee marketplace in Sidoarjo. Respondents in this study are consumers who have shopped at the Shopee marketplace who are domiciled in Sidoarjo, with a sample of 80 people. Sampling in this study using non-probability sampling with purposive sampling technique. The data pocessing used PLS (Partial Least Square) with the help of the SmartPLS 3.0 application. Based on the test, the result and conclusions were found that product rating, promotion, and COD service have a positive and significant effect on purchase decision at the Shopee marketplace in Sidoarjo.